TYPOLOGICAL CONTRASTS IN SYNTAX AMONG ENGLISH, RUSSIAN AND TWO TURKIC LANGUAGES - Uzakova Aziza Kuatbaevna (Bright Mind Publishing, 2025)
This article presents a comparative analysis of syntactic structures in four languages from three distinct branches: English (Germanic), Russian (Slavic), and Uzbek and Karakalpak (Turkic). The study focuses on fundamental syntactic features, such as word order, sentence structure, case marking, agreement, and the expression of grammatical relations. Despite sharing some universal traits, the languages under comparison demonstrate significant typological divergence. English and Russian, both Indo-European languages, differ notably in terms of flexibility and dependency on morphology, while Uzbek and Karakalpak, as Turkic agglutinative languages, exhibit a different syntactic logic altogether. The analysis highlights both language-specific strategies and broader cross-linguistic patterns.
Keywords: Comparative typology, syntax, English, Russian, Uzbek, Karakalpak, word order, case system, agreement, agglutination.